Creating an Online Quiz Learning Media Using Flexiquiz to Practice Essential Vocabulary for the TOEFL - Laily Nur Affini; Ajeng Setyorini; Irvani Varidha (Universitas PGRI Semarang, 2018)
The objectives of this research are (1) to explain a tutorial in creating Flexiquiz web application to essential vocabulary learning for the TOEFL, (2) to explain the Flexiquiz web application to essential vocabulary learning for the TOEFL as a learning strategy in combining the user manual with the web application for online learning, (3) to know users’ responses towards the online TOEFL quiz in essential vocabulary learning using Flexiquiz web application. This study is a qualitative research type and it is categorized as descriptive research because it is aimed to describe a learning strategy using Flexiquiz web application that can be manifested as materials integrartion. The practice questions that are available in Flexiquiz web application are taken from a book entitled “Barron’s: Essential Word for the TOEFL”. It means that the writer joined between the book with the Flexiquiz web application. The data gathered in this study are a questionnaire and a test result using Flexiquiz. The results of this study expose that the users of the Flexiquiz web application have interest to use Flexiquiz web application as online strategy to learn. Two features of Flexiquiz web application that can improve learning in vocabulary are; Grading and Review Answer. The conclusion can be drawn in this study shows the result that online learning using Flexiquiz web application is interesting, fun and easy.